Politics, practice and theory in Archeology of Peru - Kaulicke, Peter (2006)
This paper is an attempt to correlate three main aspects of Peruvian archaeology, as a mea ns to provide an evaluation of current situation. lt starts with the premise that politics usually dominates both theory and practice in different levels and modes. This politization tends to recude the scientific character (both theoretical and methodological) of the discipline, as it priorizes particularisms, the commodification, as well as the "technical" side of the profesional performance of the Peruvian archaeology. This is manifested, among other aspects, in a weak research policy and a severe reduction of scientific production.